PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 018 SUNGAI KERANJI - Hesti Rahmawati; Syahrilfuddin '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by lack of the students mathematics learning outcomes, with an average of 69.41 and KKM school that has been determined is 72. This form of research is the Classroom Action Research (CAR), which consists of two cycles. This study aims to improve mathematics learning outcomes grade fifth students at 018 primary school Sungai Keranji through the implementation of project-based learning model, implemented in the second semester at year of 2015/2016, with as many as 34 students research subject. The research instrument consisted of learning the instrument and data collection instruments. Data collection techniques were used that technique teacher and student activity observation, test engineering and technical documentation. Data analysis technique used is the analysis of teacher and student activity data and analysis of student learning outcomes. Data were analyzed using simple statistical test. After using project based learning model, there was an improvement both on teacher and student’s activity and also the mathematics learning outcomes. Activities teachers in the first cycle of 72.5% with enough categories increased in the second cycle becomes 82.5% in good categories. Activities of students in the first cycle was 72.5% with enough categories increased in the second cycle to 85% in good categories. Percentage completeness of learning outcomes in basic math score of 52.94% with an average of 69.41 increased in the first cycle of 82.35% with an average of 75.61 in the second cycle increased to 88.23% with an average of 84, 91 . improving student learning outcomes from basic score to UH I amounted to 8.93%, while improving student learning outcomes from basic score to UH II amounted to 22.83% .This shows that the implementation of a project based learning model can improve the mathematics learning outcomes grade fifth students at 018 primary school Sungai Keranji.Keywords: project based learning model, Mathematics learning outcomes